Thomas Merton and Hagia Sophia - Bras, Krijn Elzard (Studies in spirituality, 2021)
Thomas Merton (1915-1968) in 1960 wrote his "Hagia Sophia". In this prose poem he describes in lyrical language a feminine dimension of God, his Holy Wisdom with which he dwells in creation and in our inner self. This wisdom became human in Jesus Christ through the virgin Mary, and transforms humanity and creation through the Holy Ghost. In this essay I will investigate the sources Merton used for his concept of "Holy Wisdom". He found them in the Wisdom literature of Israel. But also the concept of theoria fysike of Evagrius Ponticus and Maximus Confessor inspired him. And he was deeply influenced by the Russian Sophiology of Soloviev, Bulgakov, Berdyaev and Evdokimov. Merton had several spiritual experiences and dreams about Hagia Sophia that manifested the deep existential meaning of this concept for his contemplative life. In a letter and in his famous poem he explored the different meanings of this spiritual image of unification of God and manhood. I will end with some suggestions of the relevance of Merton's conception for our spiritual questions of today.